From Stagnation to Growth: Colombian Exports from 1774 to 2000 - Meisel, Adolfo (Tiempo y economía, 2024)
The Colombian economy stagnated during most of the nineteenth century. As a result, the annual growth of its per capita gross domestic product (GDP) was around 0.4%. In contrast, during the twentieth century, the annual growth of its per capita GDP was 2.0%. A significant part of this result can be attributed to the failure of exports to grow during the nineteenth century – the average annual rate of growth of actual exports was 0.0% –, while in the twentieth century they grew at a rate of 2.0%. Two studies have been published on the subject of Colombian exports in the nineteenth century: McGreevey (1970) and Ocampo (2013). McGreevey used as a source for his historical account the records of what the main trading partners of Colombia imported. His results are flawed because of problems with reexports information and the definitions of the territorial units he used. In the case of Ocampo, although he analyzed official data published by the Colombian Ministry of Finance, the information considered did not include annual estimates, but an index for ad hoc subperiods. Thus, rates of growth cannot be estimated. In this paper I present the real annual series of per capita Colombian exports in the nineteenth and the twentieth century. Using verified information allowed me to calculate the rates of growth for different subperiods. This study, however simple, is a valuable contribution to the study of Colombian economic history.